2019
DOI: 10.1002/jmri.26977
|View full text |Cite
|
Sign up to set email alerts
|

MRI‐Based Radiomics: Associations With the Recurrence‐Free Survival of Patients With Hepatocellular Carcinoma Treated With Conventional Transcatheter Arterial Chemoembolization

Abstract: BackgroundPreoperative estimation of hepatocellular carcinoma (HCC) recurrence after conventional transcatheter arterial chemoembolization (c‐TACE) is crucial for subsequent follow‐up and therapy decisions.PurposeTo evaluate the associations of radiomics models based on pretreatment contrast‐enhanced MRI, a clinical‐radiological model and a combined model with the recurrence‐free survival (RFS) of patients with HCC after c‐TACE, and to develop a radiomics nomogram for individual RFS estimations and risk strati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
70
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 38 publications
9
70
1
Order By: Relevance
“…Interestingly, the proposed radiomics signature included two peritumoral radiomics features from arterial phase imaging rather than the portal venous phase image. This finding was consistent with previous studies, in which the presence of peritumoral enhancement in arterial phase images indicated tumor biological aggressiveness ( 22 , 35 ). Unlike previous studies, in which a peritumoral expansion distance of 1, 3, or 5 mm was set ( 21 , 22 ), we selected a radial distance of 10 mm in this study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Interestingly, the proposed radiomics signature included two peritumoral radiomics features from arterial phase imaging rather than the portal venous phase image. This finding was consistent with previous studies, in which the presence of peritumoral enhancement in arterial phase images indicated tumor biological aggressiveness ( 22 , 35 ). Unlike previous studies, in which a peritumoral expansion distance of 1, 3, or 5 mm was set ( 21 , 22 ), we selected a radial distance of 10 mm in this study.…”
Section: Discussionsupporting
confidence: 93%
“…This finding was consistent with previous studies, in which the presence of peritumoral enhancement in arterial phase images indicated tumor biological aggressiveness ( 22 , 35 ). Unlike previous studies, in which a peritumoral expansion distance of 1, 3, or 5 mm was set ( 21 , 22 ), we selected a radial distance of 10 mm in this study. According to the guideline of pathological sampling of HCC specimens, liver tissue within a 10 mm distance was defined as the adjacent peritumoral region ( 36 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Some conventional image features, such as non‐smooth tumor margin, vascular invasion, and peritumoral hypointensity on hepatobiliary phase (HBP) have been shown to be related to the prognosis of HCC 11–13 . However, the imaging features obtained by conventional MR images are limited, cannot comprehensively reflect intratumor heterogeneity, and are subjective 14,15 . Therefore, the accurate prediction of ER using such qualitative imaging characteristics remains challenging for clinicians.…”
mentioning
confidence: 99%
“…The integration of multimodal data with contrast-enhanced CT also appears effective in predicting prognosis after TACE, showing an accuracy (concordance index) of 0.73 and AUCs ranging from 0.85 to 0.90 in predicting 3-to 10-year survival [72]. The last study in 184 HCC patients used pretreatment contrast-enhanced MRI with gadodiamide for recurrence-free survival, and the combined model was the best with a C-index of 0.802 [73].…”
Section: Prediction Of Posttreatment Recurrence and Prognosis By Ct/mmentioning
confidence: 99%